The Persistence of the “Mano Dura” - Anthony Pereira and Mark Ungar (My University, 2016)
Democratic transitions in Brazil and the southern cone have had relatively little impact on patterns of policing. Close military-police ties, militarized training and doctrine, high rates of violence, a lack of effective court oversight, and continuity of organizational forms and personnel are all characteristics of the police in contemporary Argentina, Brazil, Chile, and Uruguay. Why has there been so little change in policing in these new democracies? Some scholars argue that these patterns are a legacy of recent military rule, but we argue that they are a legacy of an authoritarian state rather than just of specific authoritarian regimes. Other scholars attribute variation in new democracies to different modes of transition, but we assert that civil society support and political interests are more important than the initial transition in the enactment of police reforms (or the lack of them). Finally, we explain that the degree of police centralization powerfully influences reform efforts in these Latin American democracies.